Evidence based decision of Vietnam to join regional seed cooperation. - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
The International Potato Centre (CIP) in partnership with Vietnam Academy of Agriculture Sciences (VAAS) organized a Policy Forum in Hanoi on 10 April 2019 to discuss the importance of `Siem Reap POD’ for Vietnam. The forum expressed strong support for Vietnam joining the regional seed cooperation. Following policy forum, CIP circulated a position paper on the benefits of Vietnam joining the regional cooperation in seed sector and conducted several rounds of discussions with MARD officials.